Production of disease free seed potato tuber through optimization of planting and haulm pulling time: Enhanced maximum photosynthesis and growth for higher seed potato yield (Bangladesh Journal of Agriculture, 2023)
The time for planting and haulm pulling is very crucial for production of quality of seed potato tuber. Thus, the different planting times i.e., 15th  October, 4th  November, 24th  November, and 14th  December, and haulm pulling (HP) at 68, 75, 82, and 89 days after planting (DAP) were evaluated to find out the suitable planting time and haulm pulling time for disease-free potato seed production. This study was conducted in the research field of the Plant Pathology Department, Hajee Mohammad Danesh Science and Technology University (HSTU), Dinajpur during 2016-2017. The maximum seed potato tuber yield (23.9 ton/ha) was recorded from 4th  November planting time with haulm pulling at 82 days after planting. The findings also exhibited that the minimum disease infestation was observed in the same treatment combinations which enhanced the maximum photosynthesis and growth for the plants resulting in higher seed potato yield. Farmers of subtropical regions would be benefitted if they practice these methods.Bangladesh J. Agri. 2023, 48(1): 19-39